1989
DOI: 10.2135/cropsci1989.0011183x002900030044x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Nitrogen‐Fixing Responses of Subterranean Clover to Application and Subsequent Removal of Ammonium Nitrate

Abstract: Considerable variation exists in recommendations for the use of N during establishment of forage legumes. Abundant literature documents the inhibition of N2 fixation by applied N, but few experiments determined the consequences of its subsequent removal. In this study the effects of NH4NO3 on the growth and N2 fixation of subterranean clover (Trifolium subterraneum L.) were investigated. Plants were grown in a greenhouse from seed with a modified Hoagland's solution containing 0, 2, 4, 6, 8, and 12 mM NH4NO3 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0
1

Year Published

1990
1990
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Слід також відмітити, що симбіоз бобових рослин з бульбочковими бактеріями є вигідним для макросимбіонта лише за умов дефіциту зв'язаних форм азоту, а за наявності азотовмісних сполук утворення бульбочок не завжди покращує розвиток рослин [37,[39][40][41][42][43]. Відносини бульбочкових бактерій з зовнішнім середовищем у цей період регулюються рослиною-живителем, а вплив ґрунту проявляється тільки опосередковано.…”
unclassified
“…Слід також відмітити, що симбіоз бобових рослин з бульбочковими бактеріями є вигідним для макросимбіонта лише за умов дефіциту зв'язаних форм азоту, а за наявності азотовмісних сполук утворення бульбочок не завжди покращує розвиток рослин [37,[39][40][41][42][43]. Відносини бульбочкових бактерій з зовнішнім середовищем у цей період регулюються рослиною-живителем, а вплив ґрунту проявляється тільки опосередковано.…”
unclassified
“…The use of N in legume establishment is controversial. It has been shown that the addition of low to moderate amounts of fertilizer N can be beneficial to stand establishment and early vegetative growth (2,3,9). There are N-P interactions, e.g., ifN is applied at low soil levels of P and S their deficiency may be accentuated (14).…”
mentioning
confidence: 99%